Translation and validation of the Spanish version of the Échelle de Satisfaction des Besoins Psychologiques in academic context - León, Jaime; Domínguez, Evelia; Núñez, Juan L.; Pérez, Araceli; Martín Albo, José (Anales de Psicología / Annals of Psychology, 2011)
The aim of the present research was to translate and to analyze the psychometric properties of the Spanish version of the Échelle de Satisfaction des Besoins Psychologiques using a sample of 324 university students (99 males and 225 females). Results of the confirmatory factor analysis confirmed the correlated three factor structure of the scale. Like-wise, internal consistence showed evidences of reliability. The concurrent validity was tested using a structural equation model which task orienta-tion climate predicted the three basic psychological needs and these, in turn, the intrinsic motivation. Results support preliminary the use of the Spanish version of the scale in higher education.